2021
DOI: 10.1038/s41419-021-03725-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ferritin attenuates cerebral ischaemia/reperfusion injury by inhibiting ferroptosis

Abstract: Ischaemic stroke is becoming the most common cerebral disease in aging populations, but the underlying molecular mechanism of the disease has not yet been fully elucidated. Increasing evidence has indicated that an excess of iron contributes to brain damage in cerebral ischaemia/reperfusion (I/R) injury. Although mitochondrial ferritin (FtMt) plays a critical role in iron homeostasis, the molecular function of FtMt in I/R remains unknown. We herein report that FtMt levels are upregulated in the ischaemic brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 60 publications
1
84
0
Order By: Relevance
“…Wang et al [ 87 ] reported that FtMt levels upregulate in the ischemic brains of mice. Moreover, mice lacking FtMt experience more severe brain damage and neurological deficits, accompanied by the typical molecular features of ferroptosis (increased lipid peroxidation) after cerebral ischemia-reperfusion (I/R), suggesting that FtMt plays a critical role in protecting against cerebral I/R [ 87 ].…”
Section: Mitochondrial Antioxidant Systemmentioning
confidence: 99%
“…Wang et al [ 87 ] reported that FtMt levels upregulate in the ischemic brains of mice. Moreover, mice lacking FtMt experience more severe brain damage and neurological deficits, accompanied by the typical molecular features of ferroptosis (increased lipid peroxidation) after cerebral ischemia-reperfusion (I/R), suggesting that FtMt plays a critical role in protecting against cerebral I/R [ 87 ].…”
Section: Mitochondrial Antioxidant Systemmentioning
confidence: 99%
“…In addition, Rosaria et al ( Ingrassia et al, 2012 ) observed increased expression of NF-κB-regulated 1B isoform of the divalent metal transporter-1 (1B/DMT1) in animal and cellular models of ischemic stroke, which was associated with increased iron uptake into neuronal cells. Recently, Wang et al reported that mitochondrial ferritin attenuates neuronal ferroptosis by decreasing the intracellular labile iron pool during cerebral IR injury ( Wang et al, 2021 ).…”
Section: Mechanisms Of Ferroptosis In the Pathogenesis Of Ischemic Strokementioning
confidence: 99%
“…With the deepening of research, the regulatory network of ferroptosis in stroke is gradually revealed ( Bai et al, 2020 ; DeGregorio-Rocasolano, et al, 2019 ; Zille et al, 2017 ). Ferritin reduces robust ROS production and GSH consumption; its decrease is necessary for cerebral ischemia-induced hippocampal neuronal ferroptosis through p53 and SLC7A11 in middle cerebral artery occlusion (MCAO) rats ( Chen W. et al, 2021 ), and mice lacking mitochondrial ferritin show graver brain injury and neurological deficits, accompanied by typical ferroptotic event after cerebral ischemia/reperfusion (I/R) ( Wang et al, 2021 ). ACSL4 enhances ischemic stroke by increasing ferroptosis-induced brain damage and neuroinflammation while inhibiting ACSL4, which promotes the recovery of neurological function following stroke ( Li et al, 2019 ; Chen J. et al, 2021 ; Cui et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%